PENGARUH KEGIATAN FINGER PAINTING TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 4–5 TAHUN DI PAUD BALITA BUNDA DESA PULAU PERMAI KECAMATAN TAMBANG KABUPATEN KAMPAR - ', MARDIATI; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims 1) To determine the fine motor skills of children aged 4-5 years in PAUD Balita Bunda Desa Pulau Permai District Tambang regency Kampar before the application of finger painting activities. 2) To determine the fine motor skills of children aged 4-5 years in PAUD Balita Bunda Desa Pulau Permai District Tambang Kampar regency after the application of finger painting activities. 3) To determine how much influence the application of finger painting activities against the fine motor skills of children aged 4-5 years PAUD Balita Bunda Desa Pulau Permai District Tambang regency Kampar. This type of research is an experimental research. The research sample is the child class A consisting of 14 people, 7 boys and 7 girls. Collecting data using observation and documentation. Based on the survey results revealed that 1) fine motor ability of children aged 4-5 years in PAUD Balita Bunda Desa Pulau Permai District Tambang regency Kampar before treatment is given in the form of finger painting activity is low. 2) The ability to fine motor skills of children aged 4-5 years in PAUD Balita Bunda Desa Pulau Permai District Tambang regency Kampar after the treatment is given in the form of finger painting activity has increased and is high. 3) The finger painting has a significant influence on the fine motor skills of children aged 4-5 years in PAUD Balita Bunda Desa Pulau Permai District Tambang Regency Kampar. It can be seen that there is a difference in the form of an increase in the fine motor skills of children before and after treatment. 4) Activity finger painting has the effect of 36.61% against an increase in the fine motor skills of children aged 4-5 years in early childhood Toddler Mother Desa Permai Island Mining District of Kampar